Professores de História das séries finais do ensino fundamental em início de carreira: desafios e saberes - Oliveira, Rosemeire dos Santos Cunha (2015)
The initialization to teaching is characterized by intense conflicts, uncertainties but also by moments of satisfaction, discoveries and great desire beginners to learn the profession and become better and better teachers, despite the differences experienced in this career step. This research aimed to identify and discuss issues that mark the entrance in the career of a group of history teachers of upper grades of elementary school, as well as ways of facing found to meet these requirements. For this study used a qualitative approach, through semi-structured interviews with three History of beginning teachers from the public school state of São Paulo state. The guiding axis of this survey included the entry into the teaching profession, the life cycle of teachers, challenges and difficulties faced and the knowledge they mobilized. Overall, the results of this study allow us to affirm that the early-stage teachers facing pedagogical and institutional difficulties, because they present feelings of loneliness caused by the absence of collective work, lack of experience, as well as uncertainties and insecurities that affect the carry out teaching. During the analysis, it was observed that one of the weaknesses that populate the universe of the group of beginning teachers is related to the lack of theoretical study. The results also showed that, despite being the beginning of his career an important period of the teaching life, insertion programs and monitoring of teaching does not are constituted a priority of public policy